Scenarios for Asian long-term LNG contracts before and after COVID-19 - Ason, A (Oxford Institute for Energy Studies, 2020)
The paper discusses scenarios for Asian long-term LNG contracts (LNG SPAs), taking into account the COVID-19 crisis, which, as this paper argues, will have a significant impact on the evolution of contractual arrangements in the industry. Recent market events have delivered multiple incentives for price reviews and exposed three key needs for changes to Asian LNG SPAs: (1) to abandon oil-linked pricing, (2) to increase operational flexibility, and (3) to re-examine contract adjustment mechanisms. Highlighting that the anticipated European-style wave of price review arbitrations is unlikely to materialize in Asia in the near term, the paper concludes that a transition driven by comprehensive contract reviews executed by the parties would be an optimal scenario for Asian LNG SPAs in the 2020s.